Once more about cauchy problem for evolution equation - Eidelman, S.D.; Kamin, S.; Porper, F.O. (Нелинейные граничные задачи, 2000)
The Cauchy problem for linear evolution equations and systems of equation of the arbitrary order have been a subject of a practically infinite number of papers. They contain important different information as about the uniqness and vell-posedness of Cauchy problem for equations of different structure and type as about gualitative properties of the solutions of this problem. The talk mainly concentrates on the discussion of certain concrete questions about this exstensive now sufficiently traditional, but still attractive region of investigation.